Survey and enlightenment on the wearing of protective equipment of nurses working on the front line against COVID-19. Issue 19 (14th May 2021) - Wu, Maojie; Zhang, Lin; Ning, Ning; Liu, Li; Liu, Xiaoyan
Abstract : Abstract: At present, coronavirus disease 2019 (COVID-19) remains a significant challenge for health workers around the world. This survey aims to highlight the status of the implementation of occupational protection measures for nurses working on the front line against COVID-19, and to analyze the problems in the process of wearing protective equipment. This cross-sectional study was conducted among 165 nurses who worked in COVID-19-stricken areas in China in March 2020. The questionnaire covered 3 aspects, namely: general information, the current condition of protective equipment wearing, and the wearing experience of protective equipment. A total of 160 (96.97%) valid questionnaires were collected. The average time of wearing protective equipment for the nurses surveyed was 6.38 ± 3.30 hours per working day. For first-line nurses with low risk of infection, repeated wear of protective equipment was as follows: medical protective mask 30.77%, double latex gloves 8.46%, goggles/protective mask 15.38%, protective suit 15.38%; less wear of protective equipment were as follows: work cap 7.69%, surgical mask 7.69%, single layer latex gloves 30.77%, goggles/protective mask 30.77%, and isolation gown 46.15%. For nurses who were at moderate risk of infection, repeated wear of protective equipment was as follows: surgical mask 62.22%, goggles/protective mask 68.89%, and isolation gown 65.56%; less wear: work cap 3.33%, medical protective mask 15.56%, latex gloves 15.56%, goggles/protective mask 5.56%, and protective suit 16.67%. For front-line nurses with high risk of infection, repeated wear of protective equipment was as follows: surgical mask 64.91%, more than double latex gloves 8.77%, goggles/protective mask 75.44%, isolation gown 75.44%; less wear: work cap 1.75%, medical protective mask 1.75%, latex gloves 26.32%, goggles/ protective mask 1.75%, protective suit 1.75%. The main discomforts of wearing protective equipment were poor vision due to fogging (81.88%), stuffiness (79.38%), poor mobility (74.38%), sweating (72.5%), and skin damage (61.25%). More detailed personal protection standards should be developed, and the work load of nurses should be reduced. Actions should be taken to ensure the scientific implementation of personal protective measures. To solve practical clinical problems, future protective equipment may focus on the research and development of protective equipment applicable for different risk levels, as well as the research on integrated design, fabric innovation, and reusability.